Consistency of pressure injury documentation across interfacility transfers. Issue 3 (28th July 2017) - Squitieri, Lee; Ganz, David A; Mangione, Carol M; Needleman, Jack; Romano, Patrick S; Saliba, Debra; Ko, Clifford Y; Waxman, Daniel A
Abstract : Background: Hospital-acquired pressure injuries (HAPIs) are publicly reported in the USA and used to adjust Medicare payment to acute inpatient facilities. Current methods used to identify HAPIs in administrative claims rely on hospital-reported present-on-admission (POA) data instead of prior patient health information. Objective: To study the reliability of claims data for HAPIs and pressure injury (PI) stage by evaluating diagnostic coding agreement across interfacility transfers. Methods: Using the 2012 100% Medicare Provider and Analysis Review file, we identified all fee-for-service acute inpatient discharge records with a PI diagnosis among Medicare patients 65 years and older. We then identified additional facility claims (eg, acute inpatient, long-stay inpatient or skilled nursing facility) belonging to the same patient who had either (1) admission within 1day of hospital discharge or (2) discharge within 1day of hospital admission. Multivariable logistic regression and stratified kappa statistics were used to measure coding agreement between transferring and receiving facilities in the presence or absence of a PI diagnosis at the time of patient transfer and PI stage category (early vs advanced). Results: In our comparison of claims data between transferring and receiving facilities, we observed poor agreement in the presence or absence of a PI diagnosis at the time of transfer (36.3%, kappa=0.03) and poor agreement in PI stage category (74.3%, kappa=0.17). Among transfers with a POA PI reported by the receiving hospital, only 34.0% had a PI documented at the prior transferring facility. Conclusions: The observed discordance in PI documentation and staging between transferring and receiving facilities may indicate inaccuracy of HAPI identification in claims data. Future research should evaluate the accuracy of hospital-reported POA data and its impact on PI quality measurement.